DINAMIKA PERDAGANGAN EMAS DAN BUDAK DI GORONTALO ABAD XVIII-XIX - Retno Sekarningrum; Hasanuddin Hasanuddin (Handep: Jurnal Sejarah dan Budaya, 2023)
As a hub between major ports such as Malacca, Singapore, Ternate, and Makassar, Gorontalo plays a crucial role in the shipping and trade networks of the northern region of Sulawesi. This condition was strengthened by the availability of numerous commodities, especially gold, and enslaved people. These two essential commodities had been exported, mainly by Bugis and Mandar traders, to the international market since the 16th century. Studies on the development of the Gorontalo port have received less attention from historians who only focused on the role of large ports. This paper focuses on the development of Gorontalo port in exporting gold and enslaved people in the 18th to 19th centuries. By implementing the historical method, which comprises heuristics, criticism, interpretation, and historiography, this paper points out that the development had its dynamics. Bugis and Mandar traders reflected this dynamic when they lost access to trade in gold and the enslaved people in Gorontalo since the VOC trade monopoly in the seventeenth century. The monopoly led to the vulnerability of shipping-trade activities around Gorontalo to rampant piracy by pirates and smuggling.